Considering the Effectiveness of Circulars: Finding Alternative of Medium Public Communication - Rasji, Rasji; Paramita, Sinta; Pandrianto, Nigar (Jurnal Komunikasi, 2022)
Indonesia has laws and regulations that regulate people's behavior. Therefore, the government must communicate effectively with the community, so that they can obey it. In order for the implementation of legislation to be more effective, the government issues circulars addressed to the public. This circular contains technical information or messages that need to be carried out by the public. This article discusses the effectiveness of government legal communication to the public through circulars. This research approach is quantitative by conducting surveys and normative observations of secondary data in the form of circulars, expert views from various references, and regulations related to circulars. The results showed that the government's legal communication to the public through circulars was mostly effective. This is because circulars made by government officials are more of a regulatory nature (as a regulation), and a small part are stipulating (as a stipulation). This circular is a one-sided message from government officials to other officials or the general public as communicants. The nature of regulating circular letters can be in the form of orders or recommendations that are mandatory or which can be carried out by the communicant. However, the public has the right not to implement the government's message if the contents of the circular contradict the applicable regulations. This is done through a judicial review process. However, in general, government circulars are understood, accepted and implemented by the public